VRx@Home protocol: A virtual reality at-home intervention for persons living with dementia and their care partners - Di Qi; Lora Appel; Raheleh Saryazdi; Samantha Lewis-Fung; Lou-Anne Carsault; Eduardo Garcia-Giler; Jennifer L Campos (BMJ Open)
Introduction Virtual reality (VR) technology is increasingly used by researchers and healthcare professionals as a therapeutic intervention to improve the quality of life of persons living with dementia (PLwD). However, most VR interventions to date have mainly been explored in long-term or community care settings, with fewer being explored at home. Setting is important, given that the majority of PLwD live at home and are cared for by their family care partners. One of the challenges affecting PLwD and care partner relationships is barriers in communication, which can lead to social isolation and poor quality of life for both parties. Thus, the goal of the proposed project is to explore whether an immersive, multisensory VR intervention can facilitate communication between PLwD and their care partners and, in turn, enhance personal relationships and improve well-being.Methods and analysis Thirty dyads comprised of PLwD and their family/friend care partners will participate in this at-home intervention. Their interactions will be recorded as they experience a series of 360° videos together (eg, concert, travel) either using a VR headset (PLwD) with a paired tablet (care partner) or using only a tablet together. The two conditions will allow us to compare immersive VR technology to more common non-immersive tablet-based technology. The study will begin with at-home training and baseline data collection. The intervention will then take place over a 4-week period, with the two conditions (VR vs tablet-only) experienced 2 weeks each. A comprehensive set of measures will be employed to assess the quality and quantity of dyadic interactions, such as verbal/non-verbal language (eg, informativity, gestures) and self-reported measures of well-being and quality of life.Ethics and dissemination Ethical approval for the study was granted by the University Health Network (#21–5701). Findings will be shared with all stakeholders through peer-reviewed publications and presentations.Clinical registration This study has been registered on clinicaltrials.gov (NCT06568211).